REVITALISASI SENI TRADISI DI RANCAKALONG SUMEDANG JAWA BARAT - Sumiati, Lilis; Budi, Dinda Satya Upaja (Abdi Seni, 2024)
The Sumedang style Wayang dance is a monumental work created by Raden Ono Lesmana Kartadikusumah in the 1930s. After surviving for around 90 years, there is one dance that has been recognized as part of Indonesia's Intangible Cultural Heritage (WBTB) in 2022, namely the Jayengrana Dance. Apart from dancing, Sumedang has a natural wealth of bamboo which has the potential to be developed towards a creative economy. Based on these two factors, motivated to do Community Service (PKM) in Rancakalong. The choice of place was considered on the basis of the availability of potential human resources and natural resources and as a continuation of the ISBI Bandung student street vendors.The method that will be applied in this PKM, uses the Participation Action Research (PAR) method. This method has continuity because it contains cycles of participation, research, and action. Participation is a form of caring attitude to spread the Jayengrana Dance again and build a community of bamboo musical instrument craftsmen. This form of concern is motivated by previous research. Then action is a form of activity in conducting PKM in the form of revitalization.This PKM focused on two forms of activity, namely the Jayengrana Dance training and the Workshop on Making Bamboo Musical Instruments which textually and contextually became an important part of the Sumedang community, especially the course participants who were members of the Arimbi Studio and the same time empowered the Sumedang Rancakalong Geotheater. The results of this training were then evaluated internally in the form of tides and flashmobs.